ABO Blood Groups Associated with Cancer Type Distribution in Iraqi Patients: Golongan Darah ABO Terkait dengan Distribusi Jenis Kanker pada Pasien Irak - Al-Fahadi, Nabeel Hamdulla Aziz; Najim, Ahmad Hazim; Abd-Ameer, Mustafa; Osama, Yusouf (Academia Open, 2025)
Background: Cancer remains a major global health challenge, characterized by the uncontrolled proliferation of abnormal cells. Specific Background: Emerging research suggests that ABO blood types may influence individual susceptibility to various cancers through immunological mechanisms. Knowledge Gap: However, limited studies have investigated the distribution and association of ABO blood groups with specific cancer types in the Iraqi population. Aim: This study aims to examine the relationship between ABO blood types and cancer risk among patients in Mosul, Iraq. Results: Data from 317 cancer patients revealed that blood group O was most prevalent among individuals with breast and colon cancer, while blood group A showed higher frequencies in lung and stomach cancers. Among leukemia cases, type O was predominant, especially in acute lymphocytic leukemia. Novelty: This study is one of the first in Iraq to explore the correlation between ABO blood groups and a spectrum of malignancies, providing region-specific insights into cancer epidemiology. Implications: Findings support the potential role of blood type as a biomarker for cancer susceptibility, offering a foundation for risk-based screening and personalized intervention strategies. Further genetic and longitudinal studies are warranted to clarify underlying mechanisms and enhance cancer prevention efforts. Highlights: Blood type O linked to breast and colon cancer cases. Type A more common in lung and stomach cancer. ABO typing aids early cancer risk identification. Keywords: ABO blood group, cancer risk, leukemia, tumor classification, personalized medicine